The proteasome activator REGγ counteracts immunoproteasome expression and autoimmunity. (September 2019) - Yao, Liangfang; Zhou, Lei; Xuan, Yang; Zhang, Pei; Wang, Xiaoshuang; Wang, Tianzhen; Meng, Tianyuan; Xue, Yanyan; Ma, Xueqing; Shah, Abdus Saboor; Shang, Shiwang; Ma, Xinglong; et al.
Abstract: For quite a long time, the 11S proteasome activator REGɑ and REGβ, but not REGγ, are known to control immunoproteasome and promote antigen processing. Here, we demonstrate that REGγ functions as an inhibitor for immunoproteasome and autoimmune disease. Depletion of REGγ promotes MHC class I-restricted presentation to prime CD8 + T cells in vitro and in vivo . Mice deficient for REGγ have elevation of CD8 + T cells and DCs, and develop age-related spontaneous autoimmune symptoms. Mechanistically, REGγ specifically interacts with phosphorylated STAT3 and promotes its degradation in vitro and in cells. Inhibition of STAT3 dramatically attenuates levels of LMP2/LMP7 and antigen presentation in cells lacking REGγ. Importantly, treatment with STAT3 or LMP2/7 inhibitor prevented accumulation of immune complex in REGγ −/− kidney. Moreover, REGγ −/− mice also expedites Pristane-induced lupus. Bioinformatics and immunohistological analyses of clinical samples have correlated lower expression of REGγ with enhanced expression of phosphorylated STAT3, LMP2 and LMP7 in human Lupus Nephritis. Collectively, our results support the concept that REGγ is a new regulator of immunoproteasome to balance autoimmunity. Highlights: Mice deficient for REGγ develop age-related spontaneous autoimmune symptoms. REGγ represents an inhibitory checkpoint for immunoproteasome. REGγ promotes degradation of phosphorylated STAT3. REGγ regulates autoimmunity partially via phosphorylated STAT3.